Genealogies of African Nationalism and the Idea of Africa - Bongani Ngqulunga (The Thinker)
The historiography of the African nationalist movement in South Africa tends to focus on the struggle for political liberation. What gets marginalised, often, is that early African nationalists envisioned their political mission as not only bringing about inclusive freedom, but also to establish what they called ‘the ‘New Africa’ or ‘the regeneration of Africa’. The purpose of this paper is to discuss critically the idea of Africa—the New Africa—that leading early African nationalist intellectuals such as Pixley ka Isaka Seme, Selope Thema, Selby Msimang, Anton Lembede and Herbert Dhlomo advocated. This paper explores commonalities and differences in their imaginings and idea of Africa, and demonstrates the significance that political and intellectual currents from the African diaspora had in shaping the notion of the ‘New Africa’ that they advocated. By focusing on this idea at the heart of the African nationalist political tradition, the paper challenges scholarship that often dismisses early African nationalists as conservative, influenced by their experiences in mission communities, or by an eagerness to become loyal subjects of the British Empire.